Analisis Capital Asset Pricing Model (CAPM): Dasar Pengambilan Keputusan Investasi Saham pada Perusahaan Sektor Perbankan - Urwah, Khaerun Nisa; Farida, Ida; Faozi, Arief Zul (Owner : Riset dan Jurnal Akuntansi, 2024)
Investing is one way to increase income. However, the reality is that not all investors can generate additional income and not all investors can manage their investments optimally. This problem arises because investors make several mistakes when investing. The purpose of this study is to classifiy between efficient stocks and inefficient stocks using the CAPM method, so that it can help investors in considering the right stock investment. The data collection techniques used are documentation and literature study. The data analysis technique used is descriptive quantitative. The results of this study indicate that PT. Allo Bank Indonesia Tbk (BBHI) shares have the highest average individual rate of return (stock return) of 0.2523 or 25.23%. PT. Allo Bank Indonesia Tbk (BBHI) has the highest beta index of 6.6166 and is an aggressive stock because beta is more than one (?>1). PT. Allo Bank Indonesia Tbk (BBHI) has the highest expected return of 0.0824 or 8.24%. The conclusion of this study states that there are 18 efficient stock issuers, namely stocks that have individual stock returns higher than the expected rate of return [Ri>E(Ri)] and 16 inefficient stocks, namely stocks that have individual returns lower than the expected rate of return [Ri<E(Ri)]